2019
DOI: 10.3389/fphys.2019.00357
|View full text |Cite
|
Sign up to set email alerts
|

The Slow Component of Oxygen Uptake and Efficiency in Resistance Exercises: A Comparison With Endurance Exercises

Abstract: Introduction There is a lack of information regarding the slow component of oxygen uptake (VO 2 sc) and efficiency/economy in resistance exercises despite the crucial role played in endurance performance. Purpose this study aimed to compare the VO 2 sc, efficiency/economy, metabolic, cardiorespiratory responses, rating of perceived effort and mechanical fatigue between cycling and half-squat (HS) exercises during a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 45 publications
0
21
0
2
Order By: Relevance
“…In this case, an important bias would occur when comparing ventilatory efficiency, cardiorespiratory and metabolic responses between both exercises. However, the results reported by our research group in a recent study [49] revealed that the detection of the LT in both exercises using this same methodology could occur at a similar metabolic instant and relative intensity according to the criteria defined by Binder et al [50]. In both incremental tests, an equivalent load intensity was produced at the LT, however, cardiorespiratory response was higher in cycle ergometer than in HS exercise during constant-load tests.…”
Section: Discussionmentioning
confidence: 61%
“…In this case, an important bias would occur when comparing ventilatory efficiency, cardiorespiratory and metabolic responses between both exercises. However, the results reported by our research group in a recent study [49] revealed that the detection of the LT in both exercises using this same methodology could occur at a similar metabolic instant and relative intensity according to the criteria defined by Binder et al [50]. In both incremental tests, an equivalent load intensity was produced at the LT, however, cardiorespiratory response was higher in cycle ergometer than in HS exercise during constant-load tests.…”
Section: Discussionmentioning
confidence: 61%
“…1RM test protocol was performed as in previous studies [44,45] according to the guidelines established by Baechle and Earle [46]. The FBS test included a general and specific warm-up for all subjects.…”
Section: One-repetition Maximum Full Back Squat Testmentioning
confidence: 99%
“…Lower limb fatigue was determined by a countermovement jump (CMJ) test. The CMJ test was performed using a force platform (Musclelab, Ergotest Technology AS, Langesund, Norway) before and after the WOD test following a method described previously [44,45]. Participants carried out 3 jumps separated by a 30-s rest, and the mean values of vertical height recorded in the 3 CMJs were used in the statistical analysis.…”
Section: Mechanical Fatiguementioning
confidence: 99%
“…Lower limb fatigue was determined by a countermovement jump (CMJ) test following a method described previously [44,45]. The CMJ test was performed using a force platform (Musclelab, Ergotest Technology AS, Langesund, Norway) before and after the WOD test.…”
Section: Mechanical Fatiguementioning
confidence: 99%